Autophagy and Exosomes: Cross-Regulated Pathways Playing Major Roles in Hepatic Stellate Cells Activation and Liver Fibrosis - Mastoridou, Eleftheria M.; Goussia, Anna C.; Glantzounis, Georgios K.; Kanavaros, Panagiotis; Charchanti, Antonia V. (Frontiers in Physiology, 2022)
Chronic liver injury, regardless of the underlying disease, results in gradual alteration of the physiological hepatic architecture and in excessive production of extracellular matrix, eventually leading to cirrhosis. Histologically, the liver is composed Liver cellular architecture consists of different cell populations, of among which hepatic stellate cells have been found to play a major role in the fibrotic process. Under normal conditions, hepatic stellate cells serve as the main storage site for vitamin A, however pathological stimuli lead to their transdifferentiation into myofibroblast cells, with autophagy being the key regulator of their activation, through lipophagy of their lipid droplets. Nevertheless, the role of autophagy in liver fibrosis is multifaceted, as increased autophagic levels have been associated with alleviation of the fibrotic process. In addition, it has been found that hepatic stellate cells receive paracrine stimuli from neighboring cells, such as injured hepatocytes, Kupffer cells, sinusoidal endothelial cells, which promote liver fibrosis. These stimuli have been found to be transmitted via exosomes, which are incorporated by hepatic stellate cells and can either be degraded through lysosomes or be secreted back into the extracellular space via fusion with the plasma membrane. Furthermore, it has been demonstrated that autophagy and exosomes may be concomitantly or reciprocally regulated, depending on the cellular conditions. Given that increased levels of autophagy are required to activate hepatic stellate cells, it is important to investigate whether autophagy levels decrease at later stages of hepatic stellate cell activation, leading to increased release of exosomes and further propagation of hepatic fibrosis.